(untitled) (Qawanin Jurnal Ilmu Hukum, 2022)
ABSTRAC This study aims to identify and analyze the function of the Immigration Detention Center in fulfillment the rights of foreign refugees and to identify and analyze the inhibiting factors in the implementation of the functions of the Immigration Detention Center in fulfillment the rights of Fforeign refugees. The research method used is the empirical legal research method, namely the legal case study approach and discusses the object of research by focusing on the sociological juridical aspect and using secondary data as initial data, then primary data or field data. The results of this study indicate that the Rudenim carries out the immigration function based on Presidential Regulation no. 125 of 2016 which is related to immigration arangement and supervision. Based on the Decree of the Minister of Justice and Human Rights of the Republic of Indonesia Number M.01 PR.07.04 concerning Organization and Working Procedures of Immigration Detention Centers, the Rudenim functions are detention, relocation, repatriation and deportation. Rudenim facilitates refugees in the South Sulawesi Province with funding from IOM. The inhibiting factors for the implementation of the Rudenim in the implementation of the Rudenim function in fulfillment the rights of foreign refugees are the distance between the detention center and the community house, there are many of community houses, the large number of refugees, the limited of Rudenim officers, and a limited budget. The recommendation in this study is that in carrying out the functions of the Immigtation Detention Center, it is hoped that coordination with other agencies and refugee facilitators, namely IOM, should be further improved, it is recommended that the Immigration Detention Center maximize existing human resources by increasing the number of officers in the security sector and it is hoped that the government of Indonesia through The Ministry of Law and Human Rights of the Republic of Indonesia made clear policies regarding the status of asylum seekers and refugees in Indonesia in order to maintain the stability of the country even though it has not ratified the 1951 Convention and 1967 Protocol on the Status of Refugees. ABSTRAK Penelitian ini bertujuan untuk mengetahui dan menganalisis fungsi Rumah Detensi Imigrasi dalam pemenuhan hak pengungsi Warga Negara Asing dan untuk mengetahui dan menganalisis faktor penghambat pelaksanaan fungsi Rumah Detensi Imigrasi dalam pemenuhan hak pengungsi Warga Negara Asing. Metode penelitian yang digunakan adalah metode penelitian hukum Empiris yaitu metode pendekatan studi kasus hukum dan membahas objek penelitian dengan menitikberatkan pada aspek Yuridis Sosiologis dan menggunakan data sekunder sebagai data awalnya, yang kemudian dilanjutkan dengan data primer atau data lapangan. Hasil Penelitian ini menunjukkan Rudenim menjalankan fungsi keimigrasian berdasarkan Peraturan Presiden No. 125 Tahun 2016 yaitu terkait pengelolaan dan pengawasan keimigrasian. Berdasarkan Keputusan Menteri Kehakiman dan HAM Republik Indonesia Nomor M.01-PR.07.04 tentang Organisasi dan Tata Cara Kerja Rumah Detensi Imigrasi, Fungsi Rudenim yaitu Pendetensian, Pemindahan, Pemulangan dan Pendeportasian. Rudenim memfasilitasi pengungsi yang berada di wilayah Provinsi Sulawesi Selatan dengan pembiayaan dari IOM. Faktor penghambat pelaksanaan Rudenim Makassar dalam pelaksanaan fungsi Rudenim dalam pemenuhan hak pengungsi warga negara asing yaitu jauhnya jarak rudenim dengan community house, sebaran community house yang tidak sedikit, jumlah pengungsi yang sangat banyak, terbatasnya jumlah petugas Rudenim, dan anggaran yang terbatas. Rekomendasi penelitian yaitu hendaknya dalam melaksanakan fungsi Rumah Detensi Imigrasi diharapkan koordinasi dengan instansi lainnya serta fasilitator pengungsi yaitu IOM lebih ditingkatkan lagi, disarankan agar Rumah Detensi Imigrasi untuk memaksimalkan sumber daya manusia yang ada dengan menambah jumlah petugas di bidang pengamanan serta diharapkan Pemerintah Indonesia melalui Kementerian Hukum dan HAM RI membuat kebijakan yang jelas terkait status pencari suaka dan pengungsi di Indonesia guna tetap menjaga kestabilan negara meskipun belum meratifikasi Konvensi 1951 dan Protokol 1967 tentang Status Pengungsi.